Advancements in active filler-contained polymer solid-state electrolytes for lithium-metal batteries: A concise review - Hang Ding; Mingli Wang; Xinyuan Shan; Guang Yang; Ming Tian (Supramolecular Materials)
Lithium-metal batteries (LMBs) usually are regarded as the pinnacle of next-generation energy storage due to the high specific capacity and low redox potential of the Li-metal anode. However, their development is hindered by safety hazards related to flammable electrolytes and uncontrolled side reactions within the battery. Both polymer and solid-state inorganic electrolytes, despite their potential, exhibit shortcomings that limit their practical applications. Active filler-containing polymer electrolytes (AFPEs) offer a promising solution by combining the benefits of both types. Enhanced by supramolecular interactions between the polymer matrix and active fillers, AFPEs demonstrate superior electrochemical performance over traditional polymer electrolytes. This review discusses the progress in active fillers and various polymer matrices, examining the factors that enhance performance, particularly ionic conductivity. It also outlines the future research directions of AFPEs, aiming to broaden the application of solid electrolytes in high-performance LMBs.